Penerapan Model Problem Based Learning (PBL) Berbantuan Video Animasi untuk Meningkatkan Motivasi dan Hasil Belajar Peserta Didik Kelas IV SD - Yulianti, Eva; Utami, Ratnasari Diah (FONDATIA, 2024)
Learning motivation can influence high or low learning outcomes. To increase motivation and learning outcomes, appropriate models and media are needed. This Classroom Action Research (PTK) aims to increase students' motivation and learning outcomes in Pancasila Education regarding rules and norms by applying the Problem Based Learning learning model assisted by animated videos. In this lesson, students are directed to solve problems from videos shown by the teacher with the following syntax: orientation of students to the problem, organization of students, guided individual and group investigations, developed and presented results, analyzed and evaluated the process and results of problem solving. The subjects in this research were 26 class IV students at SD Muhammadiyah 16 Surakarta. The data obtained in this research through tests, interviews and observations were then analyzed using quantitative descriptive methods. The indicator of this success is an increase in the average motivation and learning outcomes in each cycle up to the target set by the researcher. The results of this research show that the application of the PBL model is able to increase student motivation with the average observation results in cycle I = 76.50% and cycle II = 90.86%. The average interview result in cycle I= 57.66% and in cycle 2= 87.40%. Apart from that, it can also improve student learning outcomes regarding the rules and norms of learning Pancasila education. Pre-cycle data shows an average learning outcome of 64.04%, increasing to 73.65% in cycle 1, and increasing in cycle 2 to 86.54%. Thus it can be concluded that the application of the PBL model assisted by animated videos can increase student motivation and learning outcomes.